Nobility of spirit : a forgotten ideal - Riemen, Rob, 1962- (Yale University Press, 2008)
In the pages of this slim, powerful book Rob Riemen argues with passion that "nobility of spirit" is the quintessence of a civilized world. It is, as Thomas Mann believed, the sole corrective for human history. Without nobility of spirit, culture vanishes.